(untitled) (Journal of Governance and Development (JGD), 2024)
Evidence confirms that for local economic development (LED) to be successful and improve the lives of local communities, sub-national governments and for that matter local governments are supposed to play an active role in the process. To this end, the purpose of this study is to investigate the contribution of urban local government in the promotion of LED in Adama City, Ethiopia. Both quantitative and qualitative data were collected to achieve the objective of the study. Qualitative data was collected through document analysis and key informant interviews (KII). On the other hand, quantitative data was collected using a survey questionnaire developed based on five-point Likert-scales to measure the perceptions of various respondents on the contribution of urban local government in promoting LED and factor attributes for its poor contribution. While survey questionnaires were randomly distributed to target respondents, interview participants were included in the study using purposive and convenience sampling techniques. The findings of the study highlight gaps in the overall contribution of the Adama City government towards LED, which is measured in terms of the provision of infrastructure, regulating and capacitating socio-economic entities in the city, creating favourable environments for networking and businesses to flourish, facilitating credit facilities and others. The limited institutional capacity of the city government itself and the inadequate existence of favourable legal and policy environments are factors that contribute to the poor contribution of the city government to LED.